Determinants of Diarrhea in Children aged 6-59 months in North Moyo District, Sumbawa Regency, West Nusa Tenggara 2019 (Jurnal kesehatan komunitas (Journal of community health), 2021)
Background : Diarrhea in children is still a health problem that occurs in the Sumbawa Regency, especially in North Moyo district, West Nusa Tenggara. The magnitude of the problem can be seen from the high morbidity and mortality due to diarrhea. Diarrhea in children can contribute to the acute burden of disease (UNICEF, 2019). Based on the Regional Health Profile of West Nusa Tenggara Province in 2018, the prevalence of diarrhea in children aged 6-59 months in North Moyo District was 28.7% higher than the national, provincial, and district levels. The purpose of this study was to find out the corelation of determinants of diarrhea in children aged 6-59 months in North Moyo District, Sumbawa Regency.Methods : Cross sectional design was used in this study with 406 sample of children aged 6-59. Data collection was carried out by measuring weight, interview and observation.The Chi-Square test and regresi logistic were used to analysis the study.Results : The results showed the prevalence of diarrhea in children aged 6-59 months in North Moyo District was 18.7%. Statistical analysis showed that the significant corelation was the number of family members, posyandu visits, exclusive breastfeeding, how to help children diarrhea, and washing hands with soap (pvalue
Keywords: Children; diarrhea; exclusive breastfeeding; hand washing habits; the number of family members